2022
DOI: 10.1016/j.msard.2021.103450
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccine intent in appalachian patients with multiple sclerosis

Abstract: Background: Rural people with Multiple Sclerosis (PwMS) face distinctive challenges in the COVID-19 pandemic. The purpose of this study was to determine the COVID-19 vaccine intent and factors associated with vaccine hesitancy among Appalachian adults with MS. Method: We conducted a cross sectional phone and in-person survey of PwMS in a large academic center in West Virginia (WV) from February to May 2021. The study sample consists of 306 adult participants. Results: Among the 306 partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 21 publications
0
13
0
1
Order By: Relevance
“…Unsurprisingly, there is a negative association between past flu vaccination history and COVID-19 vaccine hesitancy in our study. Past history of vaccination in general impacts future decision-making concerning vaccination ( Diem et al., 2021 ; Uhr and Mateen, 2021 ; Wu et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Unsurprisingly, there is a negative association between past flu vaccination history and COVID-19 vaccine hesitancy in our study. Past history of vaccination in general impacts future decision-making concerning vaccination ( Diem et al., 2021 ; Uhr and Mateen, 2021 ; Wu et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…This extends the understanding of the interplay between COVID-19 vaccine concerns and disease stability. It has been previously reported that people with MS have concerns about the impact of the vaccine on disease relapse or progression [ 9 , 22 , 23 ]. Fear about reduced DMT efficacy and lack of DMT interaction knowledge has also been cited [ 23 , 24 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously reported that people with MS have concerns about the impact of the vaccine on disease relapse or progression [ 9 , 22 , 23 ]. Fear about reduced DMT efficacy and lack of DMT interaction knowledge has also been cited [ 23 , 24 , 25 , 26 ]. While one study has reported that participants taking DMT were more likely to be vaccinated than those who were not [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations